Modified atmosphere using propolis in post-harvested 'Eva' organic apple - Mariano-Nasser, Flávia Aparecida de Carvalho [UNESP]; Nasser, Mauricio Dominguez; Ramos, Juliana Arruda [UNESP]; Furlaneto, Karina Aparecida [UNESP]; Lundgren, Giovanna Alencar; Pagliarini, Maximiliano Kawahata; Vieites, Rogério Lopes [UNESP]; de Oliveira Orsi, Ricardo [UNESP] (Pensoft Publishers, 2020)
The objective of this study was to evaluate the efficacy of different propolis extracts in post harvesting 'EVA' organic apple, in order to prolong storage and fruit quality maintenance. After selection, fruits were sanitized with vinegar (6%) solution, dried in the air and immersed in propolis solution for 1 minute when it has been possible. Treatments were T1: Control without application; T2: 1.5% propolis alcoholic extract (1.5% EEP); T3: 2.5% propolis alcoholic extract (2.5% EEP); T4: 1.5% aqueous propolis extract (1.5% EAqP) and T5: 2.5% aqueous propolis extract (2.5% EAqP). Fruits were packed in rigid plastic boxes and stored in a cold room with temperature of 5 ± 1 °C and 85 ± 1% RH for 80 days. Every 10 days some traits were evaluated as fruit weight loss (%), respiratory activity (mL of CO2 kg of fruit-1 hour-1), luminosity, chroma, Hue angle, pH, soluble solids (°Brix), titratable acidity (g of malic acid 100g-1) and reducing and non-reducing sugars. The experimental design was completely randomized in a factorial scheme and data were submitted to F test (p <0.05) and significant interactions were deployed via regression analysis. The application of propolis extract (aqueous and alcoholic) in 'Eva' organic apple post-harvest does not prolong refrigerated storage (5 ± 1C and 85 ± 1% RH) and does not influence in fruit quality conservation.
Keywords: Coating; Malus domestica; Quality; Storage